Green and rapid access to benzocoumarins via direct benzene construction through base-mediated formal [4+2] reaction and air oxidation - Mou, Chengli (2018)
Benzocoumarin is an important structural motif widely found in natural products and synthetic molecules. Traditional methods for the synthesis of benzocoumarins and their derivatives require multiple steps, typically with an intramolecular ester forming reaction to make the lactone ring as the last step. Another major method involves transition metal‐catalyzed coupling or carbon‐hydrogen bond activation reactions starting with pre‐existing aryl frameworks in the substrates. Here we report a new strategy for the green and rapid access to benzocoumarins and their derivatives. Our method uses readily available unsaturated aldehydes and coumarins as the substrates and air as the green oxidant. The overall reaction proceeds through a formal [4+2] process to construct a new benzene ring and thus to afford benzocoumarins in essentially a single step. No metal catalysts were used; no toxic or expensive reagents were involved. The power of our new approach is further demonstrated in a concise formal total synthesis of cannabinol, a bioactive natural product.